The costs of caring and the living standards of carers - Cass, B; Thomson, C; Hill, P (My University, 2011)
This paper, written by the Social Policy Research Centre at the University of New South Wales, reviews the Australian and international literature on the costs of care. Research has shown that the role of informal carer has both direct and indirect costs to the carer. Direct costs comprise monetary expenses associated with the provision of care such as transport, additional heating and cleaning costs, and reduced spending on leisure activities. Indirect costs comprise opportunity, time and health costs. The paper examines the data available and the additional data that would be needed to analyse the direct and indirect costs of care. Most existing research fails to disaggregate the costs associated with taking on the caring role from the costs that arise due to disability. The final section of the paper assesses the living standards of carers using data from two waves of the Household, Income and Labour Dynamics in Australia (HILDA) Survey.
Social Policy Research Papers
Keywords: Carers; Finance -- Expenditure and constraints on expenditure; Finance; Income, wealth and finances; Finance; Carers; Expenditure and constraints on expenditure; Income, wealth and finance